Perkembangan Penelitian Terkait Konsolidasi, Merger dan Akuisisi pada Organisasi Bank: Analisis Bibliometrik - Angin, Matius Perangin; Saluy, Ahmad Badawi (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The increasing consolidation, mergers, and acquisitions (M&A) in the banking industry has driven the rapid growth of scientific publications, but research developments are still fragmented, so a bibliometric study is needed to map themes, trends, collaborations, and research opportunities. This study aims to map the development of research on banking M&A through bibliometric analysis. Data were obtained from the Scopus database and selected using the PRISMA 2020 guidelines, resulting in 520 publications published during the 2022–2026 period. The analysis was conducted using VOSviewer through publication trend analysis, co-authorship, keyword co-occurrence, overlay visualization, and density visualization. The results show that banking M&A research is dominated by the themes of financial performance, operational efficiency, bank consolidation, and financial stability, while fintech, market structure, market concentration, and banking supervision are emerging as the latest research focuses. On the other hand, the transformation of human capital, organizational culture, leadership, change management, and post-merger organizational integration remains relatively underexplored. This study provides a comprehensive map of the intellectual structure and development of banking M&A research and proposes a future research agenda that emphasizes the integration of organizational, technological, and human resource aspects to support the success of banking mergers.